Pulmonary lesions induced by SARS-CoV-2 infection in domestic cats. Issue 4 (July 2022) - Patania, Olivia M.; Chiba, Shiho; Halfmann, Peter J.; Hatta, Masato; Maemura, Tadashi; Bernard, Kristen A.; Kawaoka, Yoshihiro; Crawford, LaTasha K.
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of coronavirus disease 2019, which ranges from fatal disease in some to mild or subclinical in most affected individuals. Many recovered human patients report persistent respiratory signs; however, lung disease in post-acute infection is poorly understood. Our objective was to describe histologic lung lesions and viral loads following experimental SARS-CoV-2 infection in 11 cats. Microscopic evaluation at 3, 6, 10, or 28 days postinoculation (DPI) identified mild to moderate patchy interstitial pneumonia, bronchiolar epithelial damage, and occlusive histiocytic bronchiolitis. Based on immunohistochemistry, alveolar septal thickening was due to CD204-positive macrophages, fewer B and T lymphocytes, type II pneumocytes, and capillary proliferation with a relative dearth of fibrosis. In blood vessel endothelium, there was reactive hypertrophy or vacuolar degeneration and increased MHC II expression at all time points. Unexpectedly, one cat from the 28 DPI group had severe subacute regionally extensive lymphohistiocytic pneumonia with multifocal consolidation, vasculitis, and alveolar fibrin. Reverse transcriptase-quantitative polymerase chain reaction identified SARS-CoV-2 RNA within the lung at 3 and 6 DPI, and viral RNA was below the limit of detection at 10 and 28 DPI, suggesting that pulmonary lesions persist beyond detection of viral RNA. These findings clarify our comparative understanding of disease induced by SARS-CoV-2 and suggest that cats can serve as an informative model to study post-acute pulmonary sequelae.